2009
DOI: 10.1177/070674370905401102
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala and Hippocampal Volumes in Relatives of Patients with Bipolar Disorder: A High—Risk Study

Abstract: M esiotemporal structures including hippocampus and amygdala have been implicated in the pathophysiology of BD by converging evidence from structural, 1 functional neuroimaging, 2 neuropathological, 3 and neurocognitive 4 studies. Structural neuroimaging findings regarding the amygdala are markedly heterogeneous, with findings of decreased, 5-8 unchanged, 9-13 as well as increased 14-18 amygdala volumes in patients with BD relative to control subjects. Similarly, the literature regarding hippocampal volumes is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 42 publications
1
29
1
2
Order By: Relevance
“…This is in contrast to the majority of previous studies, 19,[21][22][23][24][25] as well as to 8 previous meta-analyses, [33][34][35][36][37][38][39][40] all of which reported comparable hippocampal volumes between patients with bipolar disorder and controls.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…This is in contrast to the majority of previous studies, 19,[21][22][23][24][25] as well as to 8 previous meta-analyses, [33][34][35][36][37][38][39][40] all of which reported comparable hippocampal volumes between patients with bipolar disorder and controls.…”
Section: Discussioncontrasting
confidence: 54%
“…[15][16][17][18] In contrast, studies of patients with bipolar disorder have been contradictory, with findings of mostly comparable, [19][20][21][22][23][24][25] but also smaller [26][27][28][29] or even larger [30][31][32] hippocampal volumes in patients with bipolar disorder relative to controls. As a result, all 8 published metaanalyses found preserved hippocampal volumes in patients with bipolar disorder.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, increased volume [106] and no alterations [216] in caudate volume have also been reported. Whereas there seem to be no volumetric alterations in the amygdala of relatives of patients with bipolar disorder [217,218], there are reports of reduced hippocampal volume [218] and also reports of no apparent alterations in the hippocampus [217]. Furthermore, one study observed reduced thalamic volumes in relatives of bipolar disorder patients [215].…”
Section: Gray Matter Alterations In Network Associated With Emotionamentioning
confidence: 97%